Recurrent Respiratory Papillomatosis Causing Chronic Stridor and Delayed Speech in an 18-Month-Old Boy - Adel Alharbi; Derek Drummond; Alfredo Pinto; Valerie Kirk (Canadian Respiratory Journal)
Recurrent respiratory papillomatosis is a relatively uncommon disease that presents clinically with symptoms ranging from hoarseness to severe dyspnea. Human papilloma virus types 6 and 11 are important in the etiology of papillomas and are most probably transmitted from mother to child during birth. Although spontaneous remission is frequent, pulmonary spread and/or malignant transformation resulting in death has been reported. CO2 laser evaporation of papillomas and adjuvant drug therapy using lymphoblastoid interferon-alpha are the most common treatments. However, several other treatments have been tried, with varying success. In the present report, a case of laryngeal papillomatosis presenting with chronic stridor and delayed speech is described.